Analysis of Village Fund Budget Management in Tokalimbo Village, Towuti District, East Luwu Regency - Andi Dina Fadlia Mattoreang; Nur Widya Jabal; Dian Sasmita; Asrah Anjani; Rio Kurniawan; Putri Amelia Safitri; Muttiarni (Pustaka Digital Indonesia, 2024)
This research investigates the management of village fund budgets in Tokalimbo Village, located in Towuti District, East Luwu Regency. To support village development and improve community welfare, it is very important to manage village funds. Qualitative descriptive research was used, with data collection through observation, interviews and documentation. The research results show that village fund management in Tokalimbo Village has been carried out in accordance with established regulations, but there are several obstacles, such as limited apparatus capacity and poor community participation. To overcome this obstacle, capacity building is needed through training and outreach, as well as encouraging communities to participate more actively in planning and implementing village programs. Therefore, it is hoped that village funds will be managed more efficiently and provide the greatest benefits for the people of Tokalimbo Village.